Khulu' sebagai Perlindungan Wanita dalam Perspektif Hadis - Anisa Fitri; Sowfiah Handini Dwi Wan Tri; Zikri Darussamin (BAMALA Institute, 2026)
Marriage is a sacred bond aimed at establishing a harmonious family life filled with love, affection, and tranquility. However, many women find themselves trapped in marriages that no their well-being, This situation makes the study of khulu’ as a mechanism for women’s protection in islam an important and urgent subject of inguiry. This study aims to analyze the concept of khulu’ from the perspective of prophetic hadiths as a form of protection for women’s rights in terminating a marriage that can no longer be maintained. This study employs a library research method with a descriptive-analytical approach through examination of prophetic hadiths, the Qur’an, and the opinions of Islamic jurusts concerning khulu’. The findings indicate that khulu’. The findings indicate that khulu’ is a right granted by islam to women to request divorce from their husbands by returning the mahr as compensation. The prophetic hadiths explicitly affirm the legitimacy of khulu’ and demonstrate that islam provides genuine protection for women in marriages that threaten their walfare. Therefore, khulu’ is not merely a mechanism for divorce, but an instrument of Islamic justice in safeguarding the rights and dignity pf women.